From boats to bushes: environmental elements supportive of children's sociodramatic play outdoors. Issue 2 (3rd March 2020) - Robertson, Natalie; Morrissey, Anne-Marie; Moore, Deborah
ABSTRACT: Sociodramatic play is a central activity of early childhood, one influenced by the nature of the environment where it occurs. Using the Smilansky Scale for the Evaluation of Dramatic and Socio Dramatic Play (Smilansky and Shefatya, 1990), this study compared the frequency and complexity of the sociodramatic play of two groups of fifteen 4–5 year old children in two preschool outdoor spaces differing in natural elements, resources, and spatial characteristics. Field notes and behaviour mapping were also employed to explore potential associations between the play characteristics, and specific elements and areas of the two spaces. Findings showed the following elements supported more frequent and complex sociodramatic play: a balanced conjunction of man-made resources and significant vegetation and natural loose parts; opportunities for seclusion and lack of overcrowding; linking pathways and open-ended design. The findings have implications for the design of outdoor spaces that support the frequency and complexity of children's sociodramatic play.